Predictors of Pneumococcal Co-infection for Patients with Pandemic (H1N1) 2009 - Mar Masiá (Emerging Infectious Diseases, 2011)
We conducted a systematic investigation of pneumococcal co-infection in patients with a diagnosis of pandemic (H1N1) 2009 and any risk factor for complications or with severity criteria. We found 14% prevalence, with one third of patients having nonpneumonic infections. A severity assessment score >1 and high C-reactive protein levels were predictors of pneumococcal co-infection.